2020
DOI: 10.1038/s41598-020-69253-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitric oxide on the GABA, polyamines, and proline in tea (Camellia sinensis) roots under cold stress

Abstract: Tea plant often suffers from low temperature induced damage during its growth. How to improve the cold resistance of tea plant is an urgent problem to be solved. Nitric oxide (NO), γ-aminobutyric acid (GABA) and proline have been proved that can improve the cold resistance of tea plants, and signal transfer and biosynthesis link between them may enhance their function. NO is an important gas signal material in plant growth, but our understanding of the effects of NO on the GABA shunt, proline and NO biosynthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 56 publications
3
26
0
Order By: Relevance
“…In our case, PAs may play a dual role; as antioxidant compounds and controller of NO biosynthesis. A similar finding was reported by Wang et al (2020); PAs concentration in tea roots showed different trend by applying exogenous NO scavenger and inhibitor. Based on these results we can assume an existing relationship between the biosynthesis of NO and its intracellular amount.…”
Section: Snp-derived No Influences Cr-elicited Stress Metabolitessupporting
confidence: 89%
See 1 more Smart Citation
“…In our case, PAs may play a dual role; as antioxidant compounds and controller of NO biosynthesis. A similar finding was reported by Wang et al (2020); PAs concentration in tea roots showed different trend by applying exogenous NO scavenger and inhibitor. Based on these results we can assume an existing relationship between the biosynthesis of NO and its intracellular amount.…”
Section: Snp-derived No Influences Cr-elicited Stress Metabolitessupporting
confidence: 89%
“…Such wider impacts have been noted in NO effects on proline and polyamines (PAs) metabolism (e.g. Wang et al 2020).…”
Section: Snp-derived No Influences Cr-elicited Stress Metabolitesmentioning
confidence: 99%
“…56 Though many studies report high levels of GABA in response to low temperature exposure, GABA content in tea roots, on the other hand, decreases under cold treatment. 57 High content of GABA is associated with plant tolerance to low temperatures. Exogenous GABA application induces an increase of endogenous GABA and improves cold tolerance in tomato seedlings, 58 banana, 59 anthurium cut-flowers, 60 and tea plants.61 Potential mechanisms by which high levels of GABA alleviate low temperature injury may be due to enhancement of plant antioxidant systems, 58,59 which reduces malondialdehyde (MDA) and ROS contents, 58 and proline accumulationmediated osmoregulation.…”
Section: Low Temperaturementioning
confidence: 99%
“… 56 Though many studies report high levels of GABA in response to low temperature exposure, GABA content in tea roots, on the other hand, decreases under cold treatment. 57 …”
Section: Abiotic and Biotic Stressmentioning
confidence: 99%
“…Low temperature (LT) is one of the momentous factors restricting plant growth and development, geographical distribution and yield expansion, and is reflected in germination, growth, development, flowering and colonization [1]. Particularly, LT often negatively regulates the reproduction process which is an indispensable process in the growth of plants, especially pollen tube germination and elongation [2].…”
Section: Introductionmentioning
confidence: 99%